La frontière vue du satellite : étude du territoire transfrontalier de Khorgos à l’aide des ondes infrarouges - Isabella Damiani (L'Espace Politique)
This study on the Khorgos border area between Kazakhstan and the People's Republic of China will aim to show a new image of territorial developments of this region, in constant evolution since the gradual opening of China towards its post-Soviet neighbors and in particular since the formalization of the Belt and Road Initiative, in 2013. This territorial analysis will be carried out by infrared satellite image processing. From near-infrared spectroscopy to thermal infrared, the use of this part of the electromagnetic spectrum will understand new elements and improve the geopolitical analysis, with information normally not reachable to the naked eye.